Functional Hierarchy of Uterotonics Required for Successful Parturition in Mice - Yoshida, Masahide (Endocrinology, 2019)
Parturition is an essential process in placental mammals for giving birth to offspring. However, the molecular machineries of parturition are not fully understood. We investigated whether oxytocin plays a crucial role in the progress of parturition in cooperation with the prostaglandin F(2α) (PGF(2α)) receptor. We first examined alterations in the expression of uterine contraction-associated genes in uteri of oxytocin receptor–deficient mice (Oxtr(−/−)) during parturition. We found that induction of cyclooxygenase (COX)-2 and connexin 43 expression was impaired in Oxtr(−/−), whereas that of PGF(2α) receptor expression was not. We next generated mice with double knockout of genes for the oxytocin receptor/oxytocin and PGF(2α) receptor (Oxtr(−/−);Ptgfr(−/−) and Oxt(−/−);Ptgfr(−/−)) and evaluated their parturition with Oxtr(−/−), Oxt(−/−), Ptgfr(−/−), and wild-type mice. In Oxtr(−/−);Ptgfr(−/−) and Oxt(−/−);Ptgfr(−/−), pregnancy rates were similar to those of other genotypes. However, normal parturition was not observed in Oxtr(−/−);Ptgfr(−/−) or Oxt(−/−);Ptgfr(−/−) because of persistent progesterone from the corpus luteum, as observed in Ptgfr(−/−). We administered RU486, a progesterone antagonist, to Ptgfr(−/−), Oxtr(−/−);Ptgfr(−/−), and Oxt(−/−);Ptgfr(−/−) on gestation day 19. These mice were able to deliver a living first pup and the parturition onset was similar to that in Ptgfr(−/−). Meanwhile, unlike Ptgfr(−/−), ∼75% of Oxtr(−/−);Ptgfr(−/−) and Oxt(−/−);Ptgfr(−/−) administered RU486 remained in labor at 24 hours after the onset of parturition. All of the pups that experienced prolonged labor died. We thus revealed that the oxytocin receptor is an upstream regulator of COX-2 and connexin 43 in the uterus during parturition and that both oxytocin/oxytocin receptor and PGF(2α) receptor are major components for successful parturition.